2003
DOI: 10.1046/j.1365-2133.2003.05461.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a locus for porokeratosis palmaris et plantaris disseminata to a 6.9-cM region at chromosome 12q24.1-24.2

Abstract: This study provides a map location for isolation of a gene causing PPPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 23 publications
1
26
1
2
Order By: Relevance
“…Although it is difficult to understand that we were not able to confirm the results recently published by Zhang et al [2004] in at least one of our own patients, it is still conceivable that our inability to detect any SSH1 mutation could be due to the apparent locus heterogeneity described in DSAP, with at least three different candidate loci reported even within patients of Chinese origin [Xia et al, 2000[Xia et al, , 2002Wei et al, 2003Wei et al, , 2004. Hence, it is possible that mutations in other genes might underlie the disease in our patients of Caucasian background and, perhaps, those of different ethnic origin, too.…”
contrasting
confidence: 75%
See 1 more Smart Citation
“…Although it is difficult to understand that we were not able to confirm the results recently published by Zhang et al [2004] in at least one of our own patients, it is still conceivable that our inability to detect any SSH1 mutation could be due to the apparent locus heterogeneity described in DSAP, with at least three different candidate loci reported even within patients of Chinese origin [Xia et al, 2000[Xia et al, , 2002Wei et al, 2003Wei et al, , 2004. Hence, it is possible that mutations in other genes might underlie the disease in our patients of Caucasian background and, perhaps, those of different ethnic origin, too.…”
contrasting
confidence: 75%
“…The disease is inherited as an autosomal dominant trait and, to date, linkage in various Chinese families was reportedly established at four different chromosomal loci, 12q23.2-q24.1 [Xia et al, 2000], 12q24.1-q24.2 [Wei et al, 2003], 15q25.1-q26.1 [Xia et al, 2002], and 18p11.3 [Wei et al, 2004], respectively. Following finemapping at chromosome 12q and screening of 30 genes within an 8.0-cM candidate interval between markers D12S330 and D12S354, Zhang et al [2004] reported in 2004 that a missense mutation, S63N, in the slingshot (SSH1) gene (MIM] 606778) and two frameshift mutations, p.Ser19CysfsX24 and p.Pro27ProfsX54, in an alternative splice variant of SSH1, designated isoform f, underlie DSAP in two Chinese families and one patient with a nonfamilial manifestation of the disease .…”
mentioning
confidence: 99%
“…Mutations within SSH1 coding and promoter region sequences were not identified in Family 1 and other four non-familial cases, though Family 1 shows linkage to the critical DSAP region at 12q24.1. Interestingly, porokeratosis palmaris plantaris et disseminata (PPPD) was also mapped to chromosome 12q24.1-24.2 (Wei et al, 2003), and may be allelic with DSAP. Thus, other gene(s) at this locus, or gene(s) at other locus/loci may cause DSAP, and at least another susceptible region on 15q25.1-26.1 has been reported in familial DSAP (Xia et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Two loci for DSAP were mapped to a 9.6-cM interval on chromosome 12q23.2-24.1 (Xia et al, 2000), and a 6.4-cM region on chromosome 15q25.1-26.1 respectively in two Chinese families (Xia et al, 2002). More recently, a locus for PPPD was mapped to a 6.9-cM interval on chromosome 12q24.1-24.2 in one Chinese family (Wei et al, 2003). Nevertheless, the genetic defects for this disorder have not been elucidated so far.…”
Section: Introductionmentioning
confidence: 99%
“…7 The occurrence of malignancies in porokeratotic lesions is clinical evidence of the pre-cancerous nature of this disease. 8 Over-expression of p53 in lesional epidermis may play a role in malignant transformation. In addition, DNA flow cytometry analysis has demonstrated abnormal DNA ploidy in the lesional epidermis of patients with different types of porokeratosis.…”
Section: Introductionmentioning
confidence: 99%